From direct democracy to the local referendum - Maciąg, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
A local referendum is an institution which has its roots in ancient gatherings, meetings and deliberations. The analysis of its genesis and evolution from the antiquity to the modern times, its extraordinary timeline and transformation, illustrates successive stages of the development of direct democracy as a result of demographic changes (population increase) as well as technological, sociological, but also legal changes. Historical and legal methodology allows seeing the archetype, observing the attempts made, their advantages and disadvantages, the paths followed in various places, and finally comparing with the current institution. This analysis indicates the most important aspects of the institution: its subjective, objective, territorial and temporal scope as well as indicates how the nature of the results changed.
Keywords: local referendum; direct democracy; referendum